Kepedulian Al-Qur’an terhadap Lingkungan Hidup: Analisis Tafsir Al-Qurthubi dan Tafsir Kementerian Agama RI - Jauhari Parma Susanto; Rusydi AM; Efendi (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
This study provides an understanding of how the Qur'an cares about the environment in the view of the interpretation of al-Qurthubi and the interpretation of the Ministry of Religion. Using a qualitative research method with a library research approach. The results of the discussion state that the interpretation of al-Qurthubi and the Ministry of Religion explain that the Qur'an talks about environmental preservation in 7 themes, namely first) with the destruction of the Environment, the knowledge and power that humans have cannot function, and human social life will also be disrupted. Second) humans are obliged to care for the earth. Third) everything that Allah created is for human needs. Fourth) humans are trusted by Allah to care for the earth by utilizing what is in it. Fifth) the destruction of nature is caused by human hands. Sixth) water is the source of all life. Seventh) Allah grows all forms of plants and fruits that humans can benefit from, the benefits that can be taken by humans are the benefits of consuming and the benefits of beauty when looking at it. All damage done by humans will be punished by law and in accordance with it, both punishments written in laws set by the local government and direct punishments given by God in the form of calamities and natural disasters.